Health Policy as a Local Political Arena in Konawe Kepulauan Regency: A Qualitative Study of the Influence of Leadership and Power in Regional Health Decision-Making - Pitrah Asfian; Cici Wulandari Asmun; Ramadhan Tosepu (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Health policy in decentralized governance is not merely a technocratic process but also a political arena shaped by leadership, power relations, actor coalitions, and negotiation among stakeholders. In island districts such as Konawe Kepulauan Regency, local political dynamics may substantially influence health decision-making processes. Objective: This study explores how leadership, power distribution, political negotiation, and actor networks shape local health policy decision-making in Kabupaten Konawe Kepulauan Regency. Methods: This study employed a qualitative case study design. Data were collected through in-depth semi-structured interviews with key informants purposively selected from government, legislature, health bureaucracy, civil society, and professional organizations, including representatives from the district government, Regional House of Representatives (DPRD), Regional Development Planning Agency (Bappeda), District Health Office, hospital leadership, NGOs, and health professional associations. Data were analyzed using thematic content analysis. Results: Five major themes emerged: (1) health policy as a networked arena dominated by executive leadership and intersectoral actors; (2) leadership and power distribution as determinants of policy priorities; (3) negotiation and political compromise in agenda setting and policy formulation; (4) budget constraints and political dynamics shaping policy implementation; and (5) policy learning and adaptive governance as drivers of policy change. Findings suggest health policy is deeply embedded in local political processes, where leadership authority, actor coalitions, and negotiation influence priority setting and implementation. Conclusion: Health policymaking in Konawe Kepulauan Regency represents a dynamic political arena where power, leadership, and institutional interaction shape policy outcomes. Strengthening collaborative governance and reducing excessive political influence in priority setting are crucial for equitable health policy development. Keywords: health policy, local politics, leadership, power relations, qualitative study, decentralization